Effectiveness of Ethanol Extract of Moringa (Moringa Oleifera L.) Leaves on Increasing Hemoglobin (Hb) Levels in White Mice - ZULFIKRI; Pratiwi Rukmana Nasution; Ernoviya (Jurnal FARMASIMED (JFM), 2026)
Background. Moringa leaves are a part of the Moringa tree that contain various macro and micronutrients as well as active substances that function as antioxidants. They contain important nutrients such as iron (Fe), calcium, vitamins, and protein. Moringa leaves are also used as the main ingredient in medicines for prevention and treatment. The iron content in Moringa leaves can be utilised in the management of anaemia. To enhance the utilisation of Moringa leaves, scientific evidence is required to prove their effect on increasing haemoglobin (Hb) levels. Objective: This study aims to determine the effectiveness of the ethanol extract of Moringa leaves on increasing haemoglobin levels in white rats induced by NaNO2 solution. Methodology. An experimental method with a pretest-posttest control group design was used. The rats were randomly divided into 5 groups, and then orally induced with NaNO2 solution for 18 days. Group I was given 0.5% Na CMC; Group II was given ethanol extract of Moringa leaves at 125 mg/kg BW/day; Group III was given ethanol extract of Moringa leaves at 250 mg/kg BW/day; Group IV was given ethanol extract of Moringa leaves at 375 mg/kg BW/day; and Group V was given Sangobion supplement at a dose of 4.5 mg/200 g BW/day. The treatments were administered for 14 days. The Hb levels of the rats were measured on days 7 and 14 after treatment. Results. The results showed that the ethanol extract of Moringa leaves (Moringa oleifera L.) at doses of 125 mg/kgBW, 250 mg/kgBW, and 375 mg/kgBW led to a significant increase in Hb values on days 7 and 14 (P < 0.05). Conclusion. The ethanol extract of Moringa leaves (Moringa oleifera L.) is effective in significantly increasing haemoglobin levels in white rats induced by NaNO₂ (p < 0.05).